Rules: Society, Language, Rationality - Koreň, Ladislav (Teorie vědy / Theory of Science, 2012)
This critical review focuses  on the topic of cooperation and rules  discussed in the book by Jaroslav  Peregrin: Človek a pravidla [Man  and Rules] (Praha: Dokořán 2011).  Except of an extensive excurse into  the structure of Peregrin's main ideas  and arguments, it aims to provide  a  systematic analysis of some central issues in this interdisciplinary  theoretical field, while discussing  some elements of Peregrin's specific  approach. In particular, it will be  argued that Peregrin's preferred  conception of rule - as propositional  knowledge to the effect that something ought to be (or ought not to be)  a certain way - cannot serve well his  purposes, if Peregrin is to keep his  evolutionary perspective on rules.